2022
DOI: 10.1038/s41598-022-24503-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential of suburban and rural areas for tourism and recreation, including individual short-term tourism under pandemic conditions

Abstract: Limited mobility and restrictions in social life caused by the COVID-19 pandemic changed people’s recreational behavior and made them seek more contact with nature. As a result, the provision of new recreational spaces in the vicinity of cities gained importance. In conditions of social distancing, rural and suburban areas can be an attractive alternative to individual short-term tourism, satisfying the need for recreation and mental and physical health restoration of urban residents. In the study a methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…This study yielded a detailed, multi-aspect description of the county under study in terms of both the factors that characterise the spatial structure of agricultural land and the distribution of property transaction prices. The use of standardised cadastral data enabled the performance of a number of spatial and statistical analyses [57], leading to important conclusions regarding the relationships between the overall condition of the spatial structure of farms [58] and their potential value as projected based on historical transactions. The demonstrated correlation between the land consolidation work demand index and transaction prices of agricultural properties does not represent a strong linear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This study yielded a detailed, multi-aspect description of the county under study in terms of both the factors that characterise the spatial structure of agricultural land and the distribution of property transaction prices. The use of standardised cadastral data enabled the performance of a number of spatial and statistical analyses [57], leading to important conclusions regarding the relationships between the overall condition of the spatial structure of farms [58] and their potential value as projected based on historical transactions. The demonstrated correlation between the land consolidation work demand index and transaction prices of agricultural properties does not represent a strong linear relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, tourism is viewed as a way of overcoming a series of problems in the development of rural areas around the world. This statement is confirmed by a more intensive development of rural tourism, which has been enhanced by the COVID-19 pandemic [23][24][25]. Rural tourism is becoming the force behind economic development and the increase in the living standard in rural communities since it is based on principles of sustainable development and the preservation of natural resources [26,27].…”
Section: Literature Reviewmentioning
confidence: 95%
“…In the course of the development of the tourism industry, it has been found that suburban tourism and rural tourism have gradually become popular leisure methods for urban residents [6]. Particularly in the context of the COVID-19 pandemic, the restrictions on travel changed people's recreational behaviors, making the countryside and suburbs more attractive options while maintaining social distancing [7]. In the post-pandemic era, tourism patterns have gradually become de-centralized, and suburban and rural scenic areas have become significantly more important to the road network [8].…”
Section: Introductionmentioning
confidence: 99%